2023
DOI: 10.1159/000528633
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Based Prediction of Survival and Recovery of Kidney Function in Acute Kidney Injury

Abstract: Background Acute kidney injury (AKI) affects increasing numbers of hospitalized patients, the prog-nosis remains poor. The diagnosis is still based on the 2012 published KDIGO criteria. Numerous new AKI biomarkers have been identified in recent years, they either reflect impaired excretory function or structural damage. The majority of markers are useful for AKI recognition under certain circumstances. Fewer data are available on the role of biomarkers in the prediction of in-hospital survival and renal recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Although it is generally believed that AKI is caused by sepsis in half of patients, it has been shown previously [ 25 ] that sepsis was responsible for only 23.6 % of AKI in affected patients. Therefore, AKI cannot be equated with S-AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is generally believed that AKI is caused by sepsis in half of patients, it has been shown previously [ 25 ] that sepsis was responsible for only 23.6 % of AKI in affected patients. Therefore, AKI cannot be equated with S-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, it may be possible to reduce mortality by taking these variables into consideration in clinical practice. Previous studies have suggested that biomarkers such as the fibrinogen-to-albumin ratio, urinary protein, urinary albumin, glycated hemoglobin, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, liver-type fatty acid-binding protein [ 25 ], and other indicators can be used to predict AKI mortality accurately. Additionally, Yoo et al [ 26 ] found that the recurrent neural network model is better than classical methods for predicting the mortality of AKI patients with continuous renal replacement therapy and improves treatment outcomes by improving important predictive factors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the data on biomarker-based mortality prediction in AKI are limited. We recently reviewed the literature [21] and identified six references that addressed the prediction of in-hospital death in acute kidney injury. Three studies included well known markers such as NGAL, KIM-1, L-FABP, and urinary (TIMP-2) x (IGFBP7) [22][23][24].…”
Section: Plos Onementioning
confidence: 99%
“…The mortality rate ranges from 10% to 20% for hospitalized patients and 44.7–53% for ICU patients [ 1 ], caused by various factors such as sepsis, trauma, cardiac surgery, nephrotoxic drugs, and underlying chronic kidney disease. However, traditional biomarkers such as serum creatinine, blood urea nitrogen, neutrophil gelatinase-associated lipocalin, and kidney injury molecule-1 (KIM-1) are limited in terms of sensitivity and specificity due to factors like age, gender, muscle mass, and hydration status, which presents a challenge for the development of effective treatments for AKI [ 2 ]. Experiences from bedside and animal studies indicated the intensive correction between AKI and tubular dysfunction, injury, or programmed death.…”
Section: Introductionmentioning
confidence: 99%